Work-Life Balance of Female Garment Workers in Bangladesh: An Imperial Investigation (Global Journal of Management and Business Research, 2015)
This study investigates the work-life balance status of female garment workers of Bangladesh. The study reveals that both family and job of female garment workers of Bangladesh are being affected due to work-life balance situation. But, familial life is more affected due to job. Thus, work interference with family is more of an issue than family interference with work for the female garment workers in Bangladesh. Finally, the study suggests good salary, reduced work load, residential facility (near to workplace/factory), transport facility, child care center, flexible working hours (roistered days off and family friendly starting and finishing times) and child schooling facility for female garment workers of Bangladesh with a view to improve their work-life balance status.
Keywords: Work life balance; female garment worker; bangladesh